Psychosocial Stimulation and Brain Plasticity in Malnourished People - Cabral S. Morris, Clare J. Lynwood (Academic Journal of Clinicians, 2023)
Review is made of the strategies and effects of sensory and environmental stimulation of malnourished individuals. The authors report evidence from experiments with animal models and studies in humans, showing the benefits of administering programmed sensory or psychosocial stimulation on neuro-behavioral functions. They also show the important role that brain plasticity can have in this process. Finally, they emphasize that electrophysiological evidence - obtained using the cortical spreading depression technique in animals - and observations in humans indicate that brain regions behave differently in this recovery. Hence, they suggest an approach to medical care for malnourished individuals taking into account these regional peculiarities of the brain.